The Analogies from the Companions M.A.B.P.W.T on Legacy and Its Law (Collection and Study) | الأقيسة الواردة عن الصحابة رضي الله عنهم في مسائل المواريث وأحكامها (جمعا ودراسة) - Yuli Yasin; Khairul Insan (Al-Zahra : Journal for Islamic and Arabic Studies, 2018)
The purposes of this research are to discover establishment of the analogy from the Sahaabah (may Allah be pleased with them) on the issues of legacy and the judgement on it, the most famous of the Sahaabah creating the fatwa and ijtihad by using the analogy in these matters, and  the analogies created by the Sahaabah M.A.B.P.W.T also. The method used in this research is the qualitative, especially by the descriptive method. The results of this research are: 1) It revealed that tradition of using analogy among sahaabah has existed since the early of their period. It was found that the Sahaabah M.A.B.P.W.T used the analogy in their jurisprudence on their sayings and fatwas on legacies. 2) almost the Ulama in the period of the Sahaabah concerning on jurisprudence are expert on legacy, some of them are the rightly guided Caliphs, Abdullah bin Abbas, Zaid ibn Thabit, Abdullah ibn Mas'ud, Abbas ibn Abd al-Muttalib, Ubay ibn Ka'b, Mu'adh ibn Jabal and Abu Musa al-Ash'ari.